Avaliação da genotoxicidade e da qualidade das águas do açude de Lucrécia/RN - Marcon, Alexandre Endres (2011)
The occurrence of human cancer in the municipality of Lucrécia (RN, Brazil) has shown high frequencies (INCA, 2007). Tests of micronucleus (MN) and nuclear abnormalities (NA) were performed to assess the genotoxic potential of water from the Lucrécia dam, which is located in a semi-arid region under the influence of crop irrigation and irregular rainfall. Water samples were collected in this source for analyzing the concentration of cyanobacteria, metals and radioactivity. Erythrocytes of Nile tilapia (Oreochromis niloticus) were collected in dam and cells of human oral mucosa in the urban area of this municipality for the bioassays of MN and NA. In fish were also analyzed concentrations of metals in samples of liver and gills. The genotoxicity tests with biological samples of fish and humans have shown significant increases in the frequencies of MN and NA (p ≤ 0.05) and are indicative of increased DNA damage in relation to the control groups. In conclusion, the results obtained from water samples and biological municipality of Lucrécia indicates that the presence of chemical and microbiological pollutants, and increase of genotoxic in human of this municipality. We suggest the implementation of advanced water treatment, to prevent further degradation of the aquatic environment and decrease in the life quality. This research of environmental quality assessment was performed in order to contemplate a multi and interdisciplinary character of this water resource and that can induce genotoxic damage in the organisms in this study region